Pengaruh Green Marketing Dan Pengetahuan Serta Kepercayaan Terhadap Keputusan Pembelian Hebalife Mataram - Firdausi, Haikal Nadhir; Sakti, Dwi Putra Buana (Universitas Mataram, 2024)
The aim of this research is to examine the influence of green marketing on purchasing decisions; testing the influence of knowledge on purchasing decisions; and test the influence of trust on purchasing decisions. The method used is explanatory research using data analysis, namely regression with a confirmatory approach. From the results of regression analysis calculations using a confirmatory approach, there is a significant relationship, namely green marketing, to purchasing decisions; knowledge of purchasing decisions and confidence in purchasing decisions for purchasing Herbalife products at NC Green Army Mataram.